قياس تأثير ألاشعة فوق البنفسجية لكاشف ألاثر النووي lexan - PC بأستخدام تقنيتي مطيافية UV-visible ومطيافية FTIR - الجبوري, حسين علي; توفيق, ندى فاضل; درويش, عصام محمد رشيد (Al-Nahrain Journal of Science, 2018)
visible and FTIR spectroscopy techniques. Lexan detector at thickness 500 μm and 1000 μm was exposed to UV-radiation from UV- lamp at UVA radiation range (0.5, 2.85, 9.5µW/cm2) and UVC radiation range (10.5, 49.7, 290 µW/cm2). The increasing of UV-radiation intensity on PC-lexan leads to increase in pseudo of optical absorption at the wave length 400-800nm, and decrease in pseudo of optical absorption at the wave number range 3250-4000 Cm-1 for UV-visible and FTIR spectroscopy techniques respectively. PC-lexan which irradiated with UV radiation leads to increase in the value of the net of optical absorption at wave number range 400-750 Cm-1 which measured at wave number 658 Cm-1 with respect to wave number 636 Cm-1 which known by [ΔA 658-636]. There was increasing in optical absorption for PC-lexan with increasing of PC-lexan thickness after measured by UV-visible technique and decreasing in optical absorption with increasing of PC-lexan thickness after measured by FTIR spectroscopy techniques. The change in optical absorption for FTIR spectroscopy at wave number 658 cm-1 was appear as a result to broken in bond of O=C=O group in PC-lexan structure. This study found was easy to use PC-lexan as a quit measurement dosimeter for UV-radiation intensity by measured UV-visible and FTIR spectroscopy at the waves- length 400-800nm or by measured [ΔA 658-636] at the wave number range 400-750 Cm-1 respectively. Keywords: PC- lexan detector, UV-radiation, UV-visible spectroscopy, FTIR.